Wearable technology in social efforts to improve health and happiness of consumer applications: A Systematic literature review - Pritam Kumar; Mastana, Amarjeet Singh; Fukushige, Aya; Wang, Yunmei (Environment and Social Psychology, 2025)
Wearable technology is quickly changing how people keep track and take care of their health, fitness, and daily tasks. Fitness trackers, health monitoring systems, and smartwatches are becoming essential instruments in modern healthcare since they give instant updates on vital signs, help with early diagnosis of health problems, and make it easier to create personalized treatment programs. The PRISMA methodology enabled the execution of this systematic literature evaluation, while the PICOC framework assisted in formulating research questions. This systematic review was also registered in the INPLASY database (INPLASY2025100053) retrospectively. Publish or Perish software (version 8) and the Scopus API key was used together to make it easier and more consistent to find relevant papers. After finding 674 possible studies in the Scopus database, filtering procedures reduced this number down to 32 papers that were thoroughly examined to see if wearable health technology may improve health and well-being. Wearables have a lot of potential, but just a few studies look at what they can do. Key findings show that wearables may make people more active, but they lose interest over time. This shows how important it is to keep coming up with new technologies, ways to motivate people, and social networks that support them. Stress tracking and sleep monitoring were two features that showed moderate gains in mental health. Sharing data with healthcare practitioners in real time typically led to more proactive care. However, flaws with privacy, data security, and user training are still matters of fears. Overall, compounding wearable data with mHealth services has a lot of potential, as long as fair access, strong data protection, and thorough user education are kept as top desired outcomes.